Pernicious anaemia and mucosal endocrine cell proliferation of the non-antral stomach. Issue 7 (July 1986) - Rode, J; Dhillon, A P; Papadaki, L; Stockbrügger, R; Thompson, R J; Moss, E; Cotton, P B
Abstract : There is a recognised association between pernicious anaemia and the development of gastric carcinoma, endocrine cell hyperplasia, and carcinoid tumour. Multiple endoscopic biopsies from the body mucosa of seven patients with pernicious anaemia showed small intestinal metaplasia with varying degrees of inflammation, fibrosis, and expansion of the lamina propria. Using conventional silver and lead stains, endocrine cells were inconspicuous. Staining for the general neural and neuroendocrine markers NSE and PGP 9.5 revealed a proliferation of endocrine cells in the epithelium and isolated clumps of endocrine cells in the lamina propria. The clumps were composed of two cell types, either small or large. Some of these endocrine cells showed gastrin, 5HT, VIP and substance P immunoreactivity of varying intensity. Ultrastructurally nine morphologically distinct types of granules were found some of which correlated with the immunohistochemistry. Some separate islands were composed solely of endocrine cells while others had a definite neural component, suggesting that the former arise from 'budding off' of enteroendocrine cells and the latter originate from the neuroendocrine cells of the lamina propria plexus. Thus there may be a dual origin of carcinoid tumours. Carcinoid tumours associated with pernicious anaemia tend to be multifocal and are infrequent. Less than 50 such cases have hitherto been reported. Our findings of endocrine cells proliferations in seven cases of pernicious anaemia indicate that this may be an adaptive change that occurs frequently and provides the basis on which carcinoids, less frequently, develop.